Comparing the Effectiveness of Different Approaches to Raise Awareness About Antimicrobial Resistance in Farmers and Veterinarians of India - Sharma, Garima; Mutua, Florence; Deka, Ram Pratim; Shome, Rajeshwari; Bandyopadhyay, Samiran; Shome, Bibek Ranjan; Kumar, Naresh Goyal; Grace, Delia; Dey, Tushar Kumar; Lindahl, Johanna (Frontiers in Public Health, 2022)
Background Antimicrobial resistance (AMR) is a global public health threat. The indiscriminate use of antibiotics in the animal health sector contributes to increasing rates of AMR and studies involving dairy farmers in India have found knowledge levels regarding antibiotics and AMR to be very low. The purpose of this study was to assess different methods to raise awareness and knowledge about AMR and antibiotic use among dairy farmers, paravets (veterinary assistants), and veterinarians. Materials and methods The study was conducted in September-December of 2018 in some parts of Haryana, Assam, Karnataka, and West Bengal. It had two parts : an intervention meeting (September-October 2018) which consisted of focus group discussions with farmers, key informant interviews with veterinary professionals along with distribution of information packages, and then a follow-up survey (November-December 2018). The villages were randomly allocated to either one of the four intervention approaches (1-FGD/KII and information package on AMR; 2-FGD/KI and information on animal health; 3- FGD/KII and information package on animal health plus information on AMR or 4; only the FGD/KII). A follow up survey was done to assess the effect of interventions. Results In total, 274 dairy farmers and 51 veterinary professionals (21 veterinarians and 30 paravets) participated in the follow-up survey. Many of the farmers and veterinary professionals who participated in the follow-up survey had been part of the intervention meetings. The average knowledge score of farmers was 7.8. It was found that the knowledge score was higher amongst farmers who had participated in the intervention meetings (p<0.05), had received intervention approach 2 (p=0.03), and approach 3 (p=0.01) and amongst female farmers (p=0.03) compared to male. The veterinary professionals had good knowledge but lacked interest in training the farmers about antimicrobial resistance. Conclusion Our research demonstrated that a higher percentage of farmers and veterinary professionals who attended the intervention meeting had improved knowledge. Dairy farmers should be regularly educated on antibiotic usage and how to avoid misusing them. Also, veterinary experts should be provided with tools and strategies to educate farmers on the use of antimicrobials.